2019
DOI: 10.5536/kjps.2019.46.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Marketing Performances according to Raising Environment in Broilers

Abstract: This study was conducted to investigate basic data of development for appropriate management system in broiler. Data such as ages at marketing, livability, body weight, etc. were collected from a total of 53 broiler farms located in Chungnam, Chungbuk, Jeollanam, Jeollabuk, Gyeongbuk. 1. Average of ages at marketing were 32 days. Those of windowless house and open-type house were 31.96 and 32.03 days, respectively. The significant difference among four seasons was highly found (P<0.001). The longest ages at ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…Refs [99][100][101][102] Antimicrobial peptides and fermented protein Improves live performance and gut health; decreases bacterial count in the intestine; enhances immunity and nutrient utilisation.…”
Section: Mode Of Action Impact On Animal Health Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Refs [99][100][101][102] Antimicrobial peptides and fermented protein Improves live performance and gut health; decreases bacterial count in the intestine; enhances immunity and nutrient utilisation.…”
Section: Mode Of Action Impact On Animal Health Referencesmentioning
confidence: 99%
“…Zhao et al 100 reported that dietary supplementation of bacteriophages significantly improved egg production of laying hens. In addition, improved body weight and feed efficiency were reported in broilers fed diets supplemented with various levels of bacteriophages 101,102 . However, further research is needed to develop practical and cost effective bacteriophage products for use in poultry production systems.…”
Section: Bacteriophagesmentioning
confidence: 99%
“…The Korean poultry industry has demonstrated continuous advancements regarding meat species compared to the past and significantly improved the environmental conditions and productivity indicators for broiler chickens ( Gallus gallus domesticus ). These advancements have resulted in a decreased feed conversion ratio and increased the daily weight gain, shortening the period necessary to achieve the broiler chicken market weight desired by the farms [ 1 ]. The average slaughter age of broilers was 31.8–32.8 days, and their slaughter weight was 1.68–1.74 kg between January and June 2020 in Korea [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data are shown as means. (1) Indicated the 7-sensor array of the electronic tongue. Table 4 shows the taste score of the samples based on the electronic tongue analysis.…”
Section: Aromatic and Taste Profilesmentioning
confidence: 99%
“…The poultry industry worldwide has grown significantly, and the production index of broiler chickens ( Gallus gallus domesticus ) has also improved, leading to the greatly improved daily weight gain of broiler chickens [ 1 ]. In regards to the broiler production indicators in South Korea, the average carcass weight of chickens with a marketing age of 35 day was 1.6 kg in 2011, whereas the average carcass weight of chickens with a marketing age of 34 day was 1.9 kg in 2020, which represents a clear improvement [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%